Noncontrast CT versus Perfusion‐Based Core Estimation in Large Vessel Occlusion: The Blood Pressure after Endovascular Stroke Therapy Study. Issue 2 (24th November 2019) - Siegler, James E.; Messé, Steven R.; Sucharew, Heidi; Kasner, Scott E.; Mehta, Tapan; Arora, Niraj; Starosciak, Amy K.; De Los Rios La Rosa, Felipe; Barnhill, Natasha R; Mistry, Akshitkumar M.; Patel, Kishan; Assad, Salman; et al.
ABSTRACT: BACKGROUND AND PURPOSE: The 2018 AHA guidelines recommend perfusion imaging to select patients with acute large vessel occlusion (LVO) for thrombectomy in the extended window. However, the relationship between noncontrast CT and CT perfusion imaging has not been sufficiently characterized >6 hours after last known normal (LKN). METHODS: From a multicenter prospective cohort of consecutive adults who underwent thrombectomy for anterior LVO 0–24 hours after LKN, we correlated baseline core volume (rCBF < 30%) and the Alberta Stroke Program Early CT Scale (ASPECTS) score. We compared perfusion findings between patients with an unfavorable ASPECTS (<6) against those with a favorable ASPECTS (≥6), and assessed findings over time. RESULTS: Of 485 enrolled patients, 177 met inclusion criteria (median age: 69 years, interquartile range [IQR: 57‐81], 49% female, median ASPECTS 8 [IQR: 6‐9], median core 10 cc [IQR: 0‐30]). ASPECTS and core volume moderately correlated ( r = −.37). A 0 cc core was observed in 54 (31%) patients, 70% of whom had ASPECTS <10. Of the 28 patients with ASPECTS <6, 3 (11%) had a 0 cc core. After adjustment for age and stroke severity, there was a lower ASPECTS for every 1 hour delay from LKN (cOR: 0.95, 95% confidence of interval [CI]: 0.91‐1.00, P = .04). There was no difference in core ( P = .51) or penumbra volumes ( P = .87) across patients over time. CONCLUSIONS: In this multicenter prospective cohort of patients who underwent thrombectomy, one‐third of patients had normal CTP core volumes despite nearly three quarters of patients showing ischemic changes on CT. This finding emphasizes the need to carefully assess both noncontrast and perfusion imaging when considering thrombectomy eligibility.